Nucleic acid sequence-based amplification methods to detect avian influenza virus - Lau, Lok-Ting (Biochem Biophys Res Commun, 2004)
Infection of poultry with highly pathogenic avian influenza virus (AIV) can be devastating in terms of flock morbidity and mortality, economic loss, and social disruption. The causative agent is confined to certain isolates of influenza A virus subtypes H5 and H7. Due to the potential of direct transfer of avian influenza to humans, continued research into rapid diagnostic tests for influenza is therefore necessary. A nucleic acid sequence-based amplification (NASBA) method was developed to detect a portion of the haemagglutinin gene of avian influenza A virus subtypes H5 and H7 irrespective of lineage. A further NASBA assay, based on the matrix gene, was able to detect examples of all known subtypes (H1–H15) of avian influenza virus. The entire nucleic acid isolation, amplification, and detection procedure was completed within 6 h. The dynamic range of the three AIV assays was five to seven orders of magnitude. The assays were sensitive and highly specific, with no cross-reactivity to phylogenetically or clinically relevant viruses. The results of the three AIV NASBA assays correlated with those obtained by viral culture in embryonated fowl’s eggs.